Fuzzy Sliding Mode Control for a Fuel Cell System - Liping Fan; Dong Huang; Minxiu Yan (Institute of Advanced Engineering and Science, 2013)
Fuel cell powered systems have low voltage and high current output characteristics. Therefore, the output voltage of the fuel cell must be stepped up by DC-DC converter. In this paper an integrated mathematical model for proton exchange membrane fuel cell power system with DC-DC converter is described by analyzing the working mechanism of the proton exchange membrane fuel cell and the boost DC-DC converter. Fuzzy sliding mode control scheme is proposed to realize stable output voltage under different loads. Simulation operations are carried out and results are compared with fuzzy control and sliding mode control. It is shown that the use of the proposed fuzzy sliding mode controller can achieve good control effect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2553